Production and quality of chitosan extracted from local fungal isolates - Paul, Dawn Carmel; Nadarajah, Kalaivani; Kader, Abdul Jalil Abdul (Penerbit Universiti Sains Malaysia, 2004)
Chitosan is a non-toxic, biodegradable, biocompatible and highly polycationic biopolymer comprising of (1,4)-linked aminodeoxy- β-D-glucan. It is rarely found in nature and is found primarily as the main component of the fungal cell wall, especially in Zygomycetes (Arcidiacono & Kaplan 1992).